Curating knowledge, creating change: University Knowledge Center, Kosovo national transition. (June 2020) - Somerville, Mary M.; Mirjamdotter, Anita; Harjizi, Edmond; Sayyad-Abdi, Elham; Gibney, Michele; Bruce, Christine; Stoodley, Ian
A collaborative system design initiative at the University for Business and Technology in Kosovo aims to make local knowledge visible and to enhance local knowledge creation, within the university and throughout the country. Since its inception in 2015, design activities aimed to activate systems through modeling the global knowledge landscape, technology enabled systems, and human activity processes. Within the framework of Informed Systems, application of Informed Learning Theory and Information Experience Design (IXD) guided prototyping systems that informed building an institutional repository named the UBT Knowledge Center. The knowledge vision anticipates that sustained curation, organization, discovery, access, and usage processes will accelerate academic engagement, national development, and global visibility, over time and with practice to further theory-to-practice and practice-to-theory.